Relationship between Chronic urticaria and autoimmune thyroid disease - Mostafa Najafipour; Masoumeh Zareizadeh; Farzad Najafipour (Wolters Kluwer Medknow Publications, 2018)
Hives is an erythematous and itchy disease that commonly affects the trunk and the organs. Acute urticaria is a common disease and affects about 10%-20% of the population during its lifetime. In patients with chronic urticaria, about 25%-30% of cases, antithyroid peroxidase (TPO) was detected and Hashimoto's disease was diagnosed. This study aimed to evaluate the anti-TPO antibody in patients with chronic urticaria and the effect of treatment of levothyroxine on its recovery. In this study, 72 people with chronic urticaria and positive anti-TPO antibody were randomly divided into two groups. Low-dose antihistamine was administered to both groups, and the first group received levothyroxine at a dose of 50 μg/day. The severity of itching was evaluated according to the visual analog scale before and after therapy. There was no significant difference in the age, sex, thyroid-stimulating hormone (TSH), and anti-TPO between the two groups. Ninety-two patients were female. In this study, all patients took a small dose of loratadine. Relative healing was observed in both the groups. However, in a group of patients taking levothyroxine and loratadine, recovery was faster and patients with no itching were significantly more likely than the other groups. The prevalence of chronic urticaria and anti-TPO antibody in this study was very high and was due to sex hormones. Therefore, in young women with chronic urticaria, especially in refractory cases, they should be monitored for anti-TPO. Anti-TPO and TSH should be evaluated for the diagnosis and treatment of patients with urticaria or chronic angioedema. Levothyroxine therapy in hives and chronic urticaria is beneficial in the treatment of thyroid dysfunction.